Tingkat kualitas keterampilan bermain basket pemain bola basket muda - Isnaini, Lalu Moh Yudha; Saputra, Sylvana Yaka; Imansyah, Yadi; Hidayatullah, Muhammad Riyan; Anam, Khaerul (Universitas Nusantara PGRI Kediri, 2022)
The basic basketball technique is a crucial achievement for a basketball player. The purpose of this study was to determine the skill level of West Lombok basketball players in West Nusa Tenggara. This research uses survey research with a test and measurement approach, type of research is descriptive quantitative. The subjects of this study were West Lombok male basketball athletes aged 18-21 years, as many as 21 players. The instrument used is a passing test to the wall with a distance of 3 meters for 15 seconds, a shooting test for 60 seconds, and a ball dribbling test. The basketball skills test result data is divided into several categories: excellent, good, average, less, very poor, and bad. The results of this study are the Excellent category of 4 players (18.18%), the good category was shown by 14 players (63.63%), and the medium category was shown by three players (13.63%). The results of this study are that the ability to play basketball for West Lombok athletes is included in the good category. The results can provide knowledge of the condition of basketball skills so that coaches can provide a form of training that suits the player's condition.